2021
DOI: 10.1021/acsenergylett.1c00190
|View full text |Cite
|
Sign up to set email alerts
|

What is the Role of Nb in Nickel-Rich Layered Oxide Cathodes for Lithium-Ion Batteries?

Abstract: Nickel-rich layered metal oxide LiNi 1−y−z Mn y Co z O 2 (1 − y − z ≥ 0.8) materials are the most promising cathodes for next-generation lithium-ion batteries in electric vehicles. However, they lose more than 10% of their capacity on the first cycle, and interfacial/structural instability causes capacity fading. Coating and substitution are possible direct and effective solutions to solve these challenges. In this Letter, Nb coating and Nb substitution on LiNi 0.8 Mn 0.1 Co 0.1 O 2 (NMC811) is easily produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
102
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(108 citation statements)
references
References 7 publications
(14 reference statements)
5
102
0
1
Order By: Relevance
“…[ 32 ] By virtue of this surface‐enriched Ti distribution, pernicious side reactions between electrolyte and the active material might be mitigated, according to literature reports on similar functional elements, such as Y 3+ , Zr 4+ , and Nb 5+ . [ 21,35–38 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 32 ] By virtue of this surface‐enriched Ti distribution, pernicious side reactions between electrolyte and the active material might be mitigated, according to literature reports on similar functional elements, such as Y 3+ , Zr 4+ , and Nb 5+ . [ 21,35–38 ]…”
Section: Resultsmentioning
confidence: 99%
“…[ 6,7 ] Therefore, increasing efforts have been devoted to the development of cathode materials with ultrahigh Ni contents of no less than 90 mol% and reduced or zero usage of Co. Meanwhile, the challenges brought by ultrahigh‐Ni cathodes, including the aggravated electrode–electrolyte interphase deterioration, [ 7–9 ] surface rock‐salt phase (NiO) formation through lattice reconstruction, [ 10–12 ] microcrack formation leading to particle pulverization, [ 7,13,14 ] and transition metal dissolution, [ 15,16 ] are under intensive investigations with an emphasis on stabilization strategies, such as cationic doping, [ 17,18 ] surface engineering, [ 19–21 ] microstructure regulation, [ 22 ] and electrolyte optimization. [ 23,24 ] A few examples of Co‐free, ultrahigh‐Ni cathodes are LiNi 0.90 Mn 0.10 O 2 , [ 25 ] LiNi 0.90 Mn 0.05 Al 0.05 O 2 , [ 26 ] and LiNi 0.96 Mg 0.02 Mn 0.02 O 2 , [ 27 ] which all exhibit a prolonged cycled life compared to the current commercial cathodes.…”
Section: Introductionmentioning
confidence: 99%
“…However, this phenomenon does not mean that Sr can easily and uniformly enter the bulk phase of LMO, because atoms can occupy sites of other atoms on the surface of the material that originated from high temperature, and this phenomenon also occurs in other material systems. [28] As shown in Scheme 1, we designed a route to synthesize Sr-modified LMO materials by a one-step calcination route. The morphologies of LMO and modified samples were investigated by SEM.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that Nb coating/doping in NMC 811 was prepared in a one‐step heat treatment, with the coating layer to increase the capacity while doping to stabilize the layered structure. As a result, significant improvement was achieved in the 1 st capacity loss, discharge capacity, rate performance and cycling stability [73,74] …”
Section: Perspectivesmentioning
confidence: 99%